Single versus three sets resistance training on strength, power and hormonal responses among untrained men / Ali Md Nadzalan - Md Nadzalan, Ali (2013)
The optimal number of sets in resistance training for specific exercises has been of the most debated issue among the practitioners and researchers. The purpose of this study was to compare the effects of single versus three sets on muscular strength, muscular power and the selected physiological responses among untrained men. 36 untrained men were recruited in this study. Participants were randomized into 3 groups; single set (n = 12), three set (n = 12) and control group (n = 12). Muscular strength was measured by bench press and squat performance. Static strength was measured by handgrip strength test and muscular power by the vertical jump test. Serum testosterone, cortisol, alanine aminotransferase (ALT), and creatine kinase (CK) concentrations were measured before, during the third weeks and after the six weeks training program. The intervention groups were engaged in six weeks of training three times per week. Common exercises were performed to the point of achieving muscular failure for every set. Significant improvement were recorded in muscular strength and muscular performances, (p<0.05) for both the single and three set group but no significant differences were found between both the intervention groups (p>0.05). Both the single set and three set resistance training had shown significant increment of testosterone, CK and ALT (p<0.05), but no significance difference were found between these two groups (p>0.05). No significant changes were found to the cortisol level. In conclusion, single set resistance training had shown similar effects on muscular strength, muscular power, testosterone, cortisol, creatine kinase and ALT among untrained men.